Flight : the journey of Charles Lindbergh - Burleigh, Robert; Wimmer, Mike (New York : Philomel, 1991)
Describes how Charles Lindbergh achieved the remarkable feat of flying nonstop and solo from New York to Paris in 1927.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
5.4
3-6
570L
Keywords: Lindbergh, Charles A., -- 1902-1974 -- Juvenile literature; Lindbergh, Charles A., -- 1902-1974.; Transatlantic flights -- Juvenile literature; Air pilots; Transatlantic flights; Aeronautics -- Flights; Air pilots; Transatlantic flights